Boosting Vocabulary Mastery with the Hello English App: A Game-Changing Solution for EFL Learners - Hanif, Diandra; Nurchurifiani, Eva; Wiratno, Purna; Rohana; Susanti, Agus (IJLHE: International Journal of Language, Humanities, and Education, 2024)
The aim of this research was to improve students' vocabulary mastery through the use of the Hello English application for tenth-grade students at SMA Negeri 8 Bandar Lampung during the 2023/2024 academic year. This study employed the Classroom Action Research (CAR) method, which was conducted in two cycles. The subjects of this research were 35 students from class X.1. Both experimental and non-experimental data collection methods were utilized. Vocabulary tests (sections 1 and 2) were used for experimental data, while observation cards were employed for non-experimental data. Data analysis incorporated both quantitative and qualitative approaches. The results of the study indicated that the Hello English application significantly improved students' vocabulary mastery. The average test scores increased from Cycle 1 to Cycle 2. In the first cycle, 14 students (40%) met the Minimum Mastery Criterion (KKM) with an average score of 70.63 points. In the second cycle, 24 students (69%) achieved the KKM, with an average score of 73 points. Additionally, the overall class performance improved from an average score of 6.5 in the first cycle to 7.22 in the second cycle, reflecting a shift from weak to satisfactory performance. Based on these findings, it was concluded that the implementation of the Hello English application effectively enhanced vocabulary mastery among the tenth-grade students of SMA Negeri 8 Bandar Lampung. This research implies that incorporating digital learning tools such as Hello English can be an effective strategy to address language learning challenges and foster student engagement in vocabulary acquisition.